Misoprostol availability and obstetrical use in latin america and the caribbean countries - Távara Orozco, Luis (2015)
Objective: To update information on misoprostol obstetrical use in order to determine availability mapping in Latin America and the Caribbean countries. Design: Survey type study. setting: Latin America and the Caribbean countries. Participants: Public and prívate sources. Methodology: A survey semiestructured format was elaborated and sent to key Latin America and the Caribbean informers. They consulted different public and private sources in each country. Answers were ncorporated in a database to obtain frequencies of each variable studied. main outcome measures: Misoprostol trademarks, content and availability. Results: Misoprostol is obtained in different trademarks in Latin America and the Caribbean, usually in 200 μg oral tablets presentations and only one is presented as 25, 50, 100 y 200 μg vaginal tablets. Few presentations associate misoprostol to an antiinflammatory. There are 17 laboratories that produce the drug and Pfizer is the laboratory with more presence in these countries. Only four available presentations are generic and 35 specific. Medical prescription is usually obligatory, but the drug can be obtained without prescription. Pharmacies and drugstores are in charge of distribution, but it can be found in hospitals, private hospitals, pharmacies and informal market. Cost varies from one country to another and is exorbitant in countries where it is obtained backstreet. Usually regulations establish the drug is for gastrointestinal use; though in 12 countries some obstetrical indications are accepted, mainly labor induction. There have been few specific initiatives to restrain access to misoprostol but there have also been very few initiatives to facilitate its access. Notwithstanding the great publication production on misoprostol around the world, very few have been written in the region. conclusions: Misoprostol is a pharmacological agent that exists and is commercialized in Latin America and its use in Obstetrics continues spreading.